2004
DOI: 10.1577/02-021
|View full text |Cite
|
Sign up to set email alerts
|

Survival Estimates for Juvenile Fish Subjected to a Laboratory‐Generated Shear Environment

Abstract: Juvenile rainbow trout Oncorhynchus mykiss and steelhead (anadromous rainbow trout), fall (age‐0 and age‐1) and spring Chinook salmon O. tshawytscha, and American shad Alosa sapidissima were exposed to shear environments in the laboratory to establish injury–mortality thresholds based on estimates of strain rate. Fish were exposed to a submerged jet having exit velocities of 0 to 21.3 m/s, providing estimated exposure strain rates up to 1,185/s. Turbulence intensity in the area of the jet where fish were subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
107
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(114 citation statements)
references
References 6 publications
(4 reference statements)
6
107
0
1
Order By: Relevance
“…Major injury was classified as life-threatening injuries such as severe bruising, bleeding, tearing, creasing, multiple injuries, or prolonged swimming impairment, disorientation, and loss of equilibrium. These classifications followed those established by Neitzel et al (2004).…”
Section: Shear Injury Response Relationshipmentioning
confidence: 76%
See 2 more Smart Citations
“…Major injury was classified as life-threatening injuries such as severe bruising, bleeding, tearing, creasing, multiple injuries, or prolonged swimming impairment, disorientation, and loss of equilibrium. These classifications followed those established by Neitzel et al (2004).…”
Section: Shear Injury Response Relationshipmentioning
confidence: 76%
“…In a set of separate laboratory studies, juvenile fall Chinook salmon (Oncorhynchus tshawythscha) and Sensor Fish were exposed to turbulent shear flows to determine how hydraulic conditions affected fish injury response (Neitzel et al 2004). The studies were designed to establish correlation metrics between Sensor Fish measurements and live fish injuries by conducting concurrent releases in a range of turbulent shear flows.…”
Section: Shear Injury Response Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of shear flumes, where fish can be exposed to user-defined levels of shear stress created by a high pressure jet, is a useful way of identifying the upper tolerances of fish. 37,38 C. Pressure-related injuries All fish that pass through a regulator or mini hydro turbine experience pressure change, 33 the severity of which is dictated by the route of passage, type of infrastructure, and the operating head. A rapid decompression can expand gas-filled organs in the fish or cause gas in the blood to come out of solution.…”
Section: B Shear Stress Injuriesmentioning
confidence: 99%
“…Studies conducted at PNNL (Neitzel et al 2004) have shown that fish can be directly injured or killed by exposure to shear and turbulence and that temporary disability, such as stunning, increases indirect mortality by predation. These experiments related fish injuries to the fluid environment in a general manner; missing are detailed measurements of the bending and torsion of the parts of the fish body, total force acting on the fish, and how these are related to the observed injuries.…”
Section: Biomechanics Cfdmentioning
confidence: 99%